PO45 | Routine prophylaxis with PD-FX concentrate in severe inherited FX deficiency: a case report (Bleeding, Thrombosis and Vascular Biology)
Background: Severe or moderate Inherited factor X (FX) deficiency is a very rare autosomal recessive bleeding disorder affecting 1:1,000,000 individuals. FX protein is synthesized by the liver and is encoded by a gene (F10) of 27 kb located on chromosome 13, containing 8 exons. One hundred eighty mutations, most of which missense, have been identified to date. FX plasma levels above 20% are infrequently associated with bleeding and heterozygotes are usually asymptomatic. In moderate (FX 1-5%) or severe (FX <1%) deficiency bleeding manifestations can be serious including hemarthroses, hematomas, umbilical cord, gastrointestinal, and central nervous system bleeding. Severe FX deficiency may benefit from routine prophylaxis. Treatment options include the use of fresh frozen plasma (FFP) or prothrombin complex concentrate (PCC). Recently a specific plasma-derived (pd) FX concentrate (Coagadex, Kedrion Biopharma) has become available for on-demand, routine prophylaxis and perioperative treatment in people of all ages with inherited FX deficiency. We present the case of an 18-year-old boy with severe FX deficiency switched to routine prophylaxis with pd-FX.